2018
DOI: 10.1002/pa.1891
|View full text |Cite
|
Sign up to set email alerts
|

Hungry minds: Investigating the food insecurity of minority community college students

Abstract: Research on food insecurity has investigated urban environments at the neighborhood and city level but neglected the importance of college institutions. Community colleges, which serve a larger population of low‐income, food insecure, and minority students than 4‐year institutions, have been especially neglected. In this mixed methods study, we examined how 50 low‐income minority students in an urban community college access food on campus and how the features of their college foodscape shape their food insecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 61 publications
(70 reference statements)
1
17
0
Order By: Relevance
“…Students’ genre-sensitive narratives might reveal their ability or inability to resolve such college difficulties, as well as their understanding of how institutional agents or structures can influence their overall success (Bazerman, 1997). This conjecture is in accordance with research that reveals that college students can use narrative genres to interpret, find support for, and resolve problems across divergent educational institutions (Ahmed, 2017; Ahmed et al, 2019; Daiute & Kreniske, 2016; Ilieva et al, 2019; Kreniske, 2017; Todorova, 2018). Thus, diverse community college students’ narratives may signal, predict, and perhaps even influence their ability (or lack thereof) to overcome college difficulties with the help of varied support systems.…”
Section: Diversity Within Community Collegessupporting
confidence: 89%
See 2 more Smart Citations
“…Students’ genre-sensitive narratives might reveal their ability or inability to resolve such college difficulties, as well as their understanding of how institutional agents or structures can influence their overall success (Bazerman, 1997). This conjecture is in accordance with research that reveals that college students can use narrative genres to interpret, find support for, and resolve problems across divergent educational institutions (Ahmed, 2017; Ahmed et al, 2019; Daiute & Kreniske, 2016; Ilieva et al, 2019; Kreniske, 2017; Todorova, 2018). Thus, diverse community college students’ narratives may signal, predict, and perhaps even influence their ability (or lack thereof) to overcome college difficulties with the help of varied support systems.…”
Section: Diversity Within Community Collegessupporting
confidence: 89%
“…First, this work draws upon the notion of genre as dynamic social actions that people employ to meet their sociocognitive needs within their sociocultural contexts (Bakhtin, 1986; Bazerman, 1997, 2004; Berkenkotter & Huckin, 1993; Daiute, 2014; Reiff & Bawarshi, 2011; Russell, 1997; Tardy, 2003, 2016). The focus on ethnically, culturally, and linguistically diverse community college students’ use of classroom and narrative genres adds to previous research on diverse people’s use of genres to review experiences and enact sociocultural goals in relation to specific audience members (Ahmed, 2017; Ahmed et al, 2019; Beer, 2000; Daiute & Kreniske, 2016; Driscoll et al, 2020; Hyon, 2002; Ilieva et al, 2019; Jovic, 2014; Kreniske, 2017; Tardy, 2003; Todorova, 2018). This article ultimately contributes to genre-related research that indicates that genre-sensitive writing is developmental and supports diverse people’s rhetorical, academic, and socioemotional growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…He concluded that identification of food stakeholder involvement and system thinking is not enough but these must be matched with proper matching of stakeholders' strengths with appropriate system model that results is adequate food security for the community (Roggio, ). Similarly, Ilieva, Ahmed, and Yan () using college student community sample found that access to food impacts on emotional and academic development. Thus, food safety is not only important for disease prevention but also contributes to the emotional and physiological development of the consumers.…”
Section: Theoretical Framework and Conceptual Modelmentioning
confidence: 95%
“…As the affordability of postsecondary education has declined, students increasingly lack access to stable housing (e.g., Goldrick-Rab et al, 2017, 2019; Hallett & Crutchfield, 2017; Hallett & Freas, 2018) and to healthy food (e.g., Freudenberg et al, 2019; Patton-López et al, 2014; Phillips et al, 2018; Wood & Harris, 2018). Lacking basic housing and healthy food is associated with negative effects on academic, health, and social outcomes (Allen & Alleman, 2019; Hickey et al, 2019; Ilieva et al, 2019; Phillips et al, 2018). These effects include not participating in campus events or other forms of student involvement (Allen & Alleman, 2019), reporting lower academic performance and GPAs (Hickey et al, 2019), and considering dropping out of college (Phillips et al, 2018).…”
mentioning
confidence: 99%